Association of COVID-19 Case-Fatality Rate With State Health Disparity in the United States - Lee, Yu-Che; Chang, Ko-Yun; Mirsaeidi, Mehdi (Frontiers in Medicine, 2022)
Background: The disproportionate burden of COVID-19 pandemic has become a major concern in the United States (US), but the association between COVID-19 case-fatality rate (CFR) and factors influencing health outcomes at a state level has not been evaluated. Methods: We calculated COVID-19 CFR for three different waves using COVID Data Tracker from the Centers for Disease Control and Prevention. America’s Health Rankings assesses the factors that influence health outcomes to determine state’s health rankings. The association between COVID-19 CFR and state health disparities was analyzed by linear regression. Results: States with better rankings of Physical Environment were associated with lower CFR for the 1st wave (β=0.06%, R2=0.170, P=0.003). There was a paradoxical association between the 2nd wave CFR and Clinical Care (β=-0.04%, R2=0.112, P=0.017) and Overall health rankings (β=-0.03%, R2=0.096, P=0.029). For the 3rd wave, states with better rankings of Overall health factors (β=0.01%, R2=0.179, P=0.002), Social & Economic Factors (β=0.01%, R2=0.176, P=0.002), Behaviors (β=0.01%, R2=0.204, P<0.001), and Health Outcomes (β=0.01%, R2=0.163, P=0.004) were associated with lower CFR. COVID-19 vaccination coverage was also associated with state health rankings (at least one dose: β=-0.13%, R2=0.305, P<0.001; fully vaccinated: β=-0.06%, R2=0.120, P=0.014). Conclusions: These findings suggested targeted public health interventions and mitigation strategies addressing health disparities are essential to improve inequitable outcomes of COVID-19 in the US.